2017
DOI: 10.5812/zjrms.7225
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bacterial Effect of Propolis Extract in Oil Against Different Bacteria

Abstract: Background: Propolis is one of the most potent natural antibiotics. Propolis as an active natural substance is attractive due to its antimicrobial properties. Propolis has been used in folk medicine for centuries. It is known that propolis possesses anti-microbial, antioxidative, anti-ulcer and anti-tumor activities. Therefore, propolis has attracted much attention in recent years as a useful or potential substance used in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In line with the literature data, our study shown that propolis have an inhibitory effect on both groups of studied microorganisms (Ramanauskiene et al, 2009;Huang et al, 2014). The efficacy of the oily propolis extract (where MIC was 0.8%) in DMSO against Gram-positive and Gram-negative bacteria (e.g., S. aureus ATCC 25923, P. aeruginosa (PAO1), E. faecalis ATCC 29212, S. aureus S3) was relieved by Ghasemi et al (2017). Contrary to previous statements, other authors have observed that propolis is more active against Gram-positive bacteria (Mohdaly et al, 2015) and it has less influence on Gram negative ones, which can even be resistant (Ghasemi et al, 2017).…”
Section: Results Results Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In line with the literature data, our study shown that propolis have an inhibitory effect on both groups of studied microorganisms (Ramanauskiene et al, 2009;Huang et al, 2014). The efficacy of the oily propolis extract (where MIC was 0.8%) in DMSO against Gram-positive and Gram-negative bacteria (e.g., S. aureus ATCC 25923, P. aeruginosa (PAO1), E. faecalis ATCC 29212, S. aureus S3) was relieved by Ghasemi et al (2017). Contrary to previous statements, other authors have observed that propolis is more active against Gram-positive bacteria (Mohdaly et al, 2015) and it has less influence on Gram negative ones, which can even be resistant (Ghasemi et al, 2017).…”
Section: Results Results Resultssupporting
confidence: 89%
“…The efficacy of the oily propolis extract (where MIC was 0.8%) in DMSO against Gram-positive and Gram-negative bacteria (e.g., S. aureus ATCC 25923, P. aeruginosa (PAO1), E. faecalis ATCC 29212, S. aureus S3) was relieved by Ghasemi et al (2017). Contrary to previous statements, other authors have observed that propolis is more active against Gram-positive bacteria (Mohdaly et al, 2015) and it has less influence on Gram negative ones, which can even be resistant (Ghasemi et al, 2017). The same effect was observed by Al-Ani et al (2018) on propolis samples originated from different parts of Europe.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…One of them is the vegetable oil extract of propolis. Antioxidant activity of the vegetable oil extract of propolis, 30,31 antibacterial [32][33][34][35] and cytotoxic activity, 36 leukemia-HL-60, colon-HCT-8, breast-MDAMB-435 and brain-SF-295 cell lines in vitro antitumoral activity, 37 antioxidant and antipyretic activity, 38 anti-inflammatory and immunostimulant effect, 39,40 effect on chemotherapy-induced oral mucositis, 41 antiradical, 42 antifungal, 43 antidepressant, and anxiolytic effects 44 have been shown.…”
Section: Resultsmentioning
confidence: 99%
“…As a natural ingredient, propolis is proven to have antimicrobial ability without causing bacterial resistance or eliminating oral microflora (Ghasemi et al, 2017). The antimicrobial property of propolis is mainly contributed by its flavonoid compound (Przybyłek and Karpinski, 2019).…”
Section: Resultsmentioning
confidence: 99%